Efektifitas therapy aktivitas kelompok terhadap kecemasan pada lansia penderita diabetes melitus - Indarna, Asep Aep; Rahayu, Sri Mulyati (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2023)
Background: Elderly people with chronic illnesses are prone to experiencing anxiety, one of which is diabetes mellitus sufferers. Efforts made to overcome anxiety in the elderly can come from family factors, environmental factors, and group activity therapy (GAT). Purpose: To determine the effectiveness of group activity therapy (GAT on anxiety levels in elderly people with diabetes mellitus at PKM Cibiru, Bandung City. Method: With a quasi-experiment research design with a pre-posttest one-group design approach. The population of all elderly people suffering from diabetes mellitus is 40, with a sample of all elderly people suffering from diabetes mellitus of 40 taken using the total sampling method. The independent variable is group activity therapy (GAT), and the dependent variable is anxiety. The instruments used were questionnaire sheets and observation sheets. Statistical tests used the Wilcoxon test with a significance value of α = 0.05. The research results before the group activity therapy (GAT) activity from 40 respondents showed a moderate anxiety level of 65.5%. After the group activity therapy (GAT) activity, there was a ligth anxiety level of 72.5%. The Wilcoxon Sign Rank test in the treatment group showed ρ = 0.001, ρ < α. Conclusion: Meaning that group activity therapy (GAT) was effective in reducing anxiety levels in elderly people with diabetes mellitus Keywords: Anxiety; Elderly; Group Activity Therapy (GAT). Pendahuluan: Lansia dengan penyakit kronis, rentan mengalami kecemasan salah satunya adalah penderita diabetesmelitus. Upaya yang dilakukan dalam mengatasi kecemasan pada lansia bisa dari faktor keluarga, kemudian faktor lingkungan dan terapi aktivitas kelompok (TAK). Tujuan: Untuk mengetahui efektifitas terapi aktivitas kelompok (TAK) terhadap tingkat kecemasan pada lansia penderita diabetes melitus di PKM Cibiru Kota Bandung. Metode: Desain penelitianQuasy-Experiment dengan pendekatanpre posttest one group design. Populasi seluruh lansia penderita diabetes melitus sebanyak 40 orang dengan sampel seluruh lansia penderita diabetes melitussebesar 40 diambil menggunakan metode total sampling. Variabel independen terapi aktivitas kelompok (TAK), variabel dependen adalah kecemasan. Instrument yang digunakan adalah lembar kuesioner dan lembar observasi. Uji statistik menggunakan Uji Wilcoxon Sign Rankdengan nilai kemaknaan α = 0,05. Hasil: Sebelum kegiatan terapi aktivitas kelompok (TAK) dari 40 responden terdapat tingkat kecemasan sedang 65,5 %, dan setelah kegiatan terapi aktivitas kelompok (TAK)terdapat tingkat kecemasan ringan72,5 %. Uji Wilcoxon Sign Rank pada lansia penderita diabetes melitus menunjukkan ρ = 0,001, ρ<α. Simpulan: Terapi aktivitas kelompok (TAK) efektif dilakukan untuk menurunkan tingkat kecemasan pada lansia penderita diabetes melitus.